Implications of the Covid-19 pandemic for revenue generation in poor African countries - Odd-Helge Fjeldstad; Ole Therkildsen (Danish Institute for International Studies (DIIS), 2020)
In the aftermath of the Covid-19 pandemic, the need in poor countries in Africa for more revenues is obvious and growing - also because aid agencies are quite stingy in assisting them in this crisis. The pandemic's negative impact on revenues is especially pronounced in countries that are most dependent on international trade, tourism and petroleum exports. The good news is that sub-Saharan African tax collectors have performed almost as well as their peers in the much wealthier Latin America and substantially better than in South Asian countries. Increased domestic revenue mobilisation (DRM) in poor African countries is possible depending on the country's specific situation and political economy - but it will not be easy.
Keywords: 330; Coronavirus; Öffentliche Einnahmen; Afrika